PERANAN K.H. AGUS SALIM DALAM MANAJEMEN PENDIDIKAN DI KOTO GADANG TAHUN 1912-1915 - Arafah Pramasto; Dina Fahira; Safira Elfadhilah (Program Studi Manajemen Pendidikan, 2024)
K.H. Agus Salim is an Indonesian national hero known as a scholar, politician, professional and journalist. Her activism can be traced from the time of the national movement to the period of defending independence. However, there is an experience that is so unique, namely when Salim fought for education in his hometown of Koto Gadang, West Sumatra. This writing uses the biographical research method of education to highlight Salim's historical role in the field of educational management. Since childhood, Agus Salim was known to be intelligent and studious. He took all of his education at the Dutch colonial school and always excelled and was fluent in many languages (polyglot). In the midst of a discriminatory colonial education system, he succeeded in establishing the private Hollandsche Inlandsche School (HIS) with the help of non-governmental organizations in 1912. He served as an advisor and teacher. Many of the school's alumni have been successfully accepted into government advanced schools, one of the reasons being that foreign language education (Dutch) is taught from an early age. Furthermore,